Rekayasa pembuatan indikator oksigen dengan membran pemisah - Endang Warsiki; Andi Nurul Aulia Sari; Ika Amalia Kartika; Indah Yuliasih; Titi Candra Sunarti (AGROINTEK, 2024)
Oxygen indicators in food packaging can be used to monitor the shelf life and quality of the product, especially in a vacuum or modified atmosphere packaged, by sensing the indicator's color change. The mechanism of the oxygen indicator is a redox reaction which is compromised redox dye, reducing compound, and alkali compound. These substances can be formulated as a tablet/sachet or a printed layer or laminated in a polymer film. This study aimed to examine the performance of the oxygen indicator in various concentrations of glucose and NaOH. This research was carried out in 3 stages, i.e. (i) producing oxygen indicators; (ii) characterizing the oxygen indicator before it was activated, and (iii) testing the irreversibility of the indicator. The results showed that the oxygen indicator had been successfully made in two compartments of NaOH and glucose-methylene blue with LDPE as a membrane barrier. The indicator's color remains the same in blue before it was activated. It seems that the concentration of glucose and natrium oxide did not have any significant difference in the initial color of the indicator. Once the indicator was activated by pressing the NaOH compartment, the color of the indicator turned purplish, and after a long while, the indicator turned white. The concentration of NaOH and storage temperature significantly affected the turning color's acceleration. A sample in the concentration of glucose 0.2 M and NaOH 0.2 M proved irreversible with ohue values of 208.57 to 313.201.© hak cipta dilindungi undang-undang.